4-Amino-1-allenylsilanes from 4-Aminopropargylic Acetates through a Silylzincation/Elimination Sequence - Bochatay, Valentin N.; Neouchy, Zeina; Chemla, Fabrice; Ferreira, Franck; Jackowski, Olivier; Pérez-Luna, Alejandro (Synthesis, 2016)
4-Aminopropargylic acetates afford 4-amino-1-allenylsilanes upon reaction with the lithium (triorganosilyl)zincate (PhMe2Si)3ZnLi. The reaction is both stereoselective and stereospecific and proceeds through syn-silylzincation of the carbon–carbon triple bond followed by subsequent anti-β-elimination of the acetate group.
Keywords: allenes; asymmetric synthesis; diastereoselectivity; silylzincation; zincates